Improving Spatial Skills through Computer Games - Hirvasoja, Mika (2004)
Jyväskylä: University of Jyväskylä, 2004. 24 pages Bachelor s Thesis This literary review spans a time period of twenty-five years and evaluates various studies related to the effects of computer game playing on spatial ability.